Electrospun Polycaprolactone Nanofibers as a Reaction Membrane for Lateral Flow Assay - Yew, Chee Hong; Azari, Pedram; Choi, Jane; Muhamad, Farina; Pingguan-Murphy, Belinda (MDPI, 2018)
Electrospun polycaprolactone (PCL) nanofibers have emerged as a promising material in diverse biomedical applications due to their various favorable features. However, their application in the field of biosensors such as point-of-care lateral flow assays (LFA) has not been investigated. The present study demonstrates the use of electrospun PCL nanofibers as a reaction membrane for LFA. Electrospun PCL nanofibers were treated with NaOH solution for different concentrations and durations to achieve a desirable flow rate and optimum detection sensitivity in nucleic acid-based LFA. It was observed that the concentration of NaOH does not affect the physical properties of nanofibers, including average fiber diameter, average pore size and porosity. However, interestingly, a significant reduction of the water contact angle was observed due to the generation of hydroxyl and carboxyl groups on the nanofibers, which increased their hydrophilicity. The optimally treated nanofibers were able to detect synthetic Zika viral DNA (as a model analyte) sensitively with a detection limit of 0.5 nM. Collectively, the benefits such as low-cost of fabrication, ease of modification, porous nanofibrous structures and tunability of flow rate make PCL nanofibers a versatile alternative to nitrocellulose membrane in LFA applications. This material offers tremendous potential for a broad range of point-of-care applications.